2008
DOI: 10.1097/prs.0b013e318185d370
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Age-Related Intraorbital Fat Herniation through Computed Tomography

Abstract: The authors found that although the amount of lower eyelid fat varies greatly between individuals, the process of lower eyelid fat herniation does occur. It retains a steady incline after the third decade of life and slows at approximately age 70. In the authors' study, ocular globe position appears unrelated to this process of herniation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…[6][7][8][9][10][11][12]23 Other studies have examined age-related volumetric changes in the facial soft tissue and described an increase in the orbital fat and lower eyelid fat, as well as selective atrophy in the cheek fat associated with increasing patient age. 1,[24][25][26][27] While prior studies have described the repositioning of facial soft tissues and the volume changes in the facial fat as primary contributors to the appearance of an older face, it is also possible that specific, age-related changes in facial tissue properties also contribute to the findings associated with an older appearing face.…”
Section: Introductionmentioning
confidence: 81%
“…[6][7][8][9][10][11][12]23 Other studies have examined age-related volumetric changes in the facial soft tissue and described an increase in the orbital fat and lower eyelid fat, as well as selective atrophy in the cheek fat associated with increasing patient age. 1,[24][25][26][27] While prior studies have described the repositioning of facial soft tissues and the volume changes in the facial fat as primary contributors to the appearance of an older face, it is also possible that specific, age-related changes in facial tissue properties also contribute to the findings associated with an older appearing face.…”
Section: Introductionmentioning
confidence: 81%
“…Several studies have measured globe position in healthy persons, SCS patients, Graves patients or patients with ophthalmic problems (Chen et al, 2008;Lee et al, 2001;Ozgen and Ariyurek, 1998;Sheikh et al, 2007). Usually in these studies a line was drawn between the most anterior points of the lateral orbital rims, using an axial CT-slice at midglobe level.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the use of MDCT and advancements in image analysis technology have made it feasible to create 3D CT images from routine images. Three-dimensional CT and reconstructed CT images provide detailed anatomic information [68]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Furnas [5] reported that baggy eyelids are attributable to laxity in the orbicularis oculi muscle. Using computed tomography (CT), Chen et al [6] described the relationship between intraorbital fat herniation or orbital fat prolapse and age. To identify the cause of baggy eyelids by diagnostic imaging, we studied the relationship between orbicularis oculi muscle thickness, orbital fat prolapse length, and age.…”
mentioning
confidence: 99%